Stress test of lithographic vertical‐cavity surface‐emitting lasers under extreme operating conditions. Issue 16 (1st August 2015) - Yang, Xu; Zhao, Guowei; Li, Mingxin; Deppe, Dennis
Abstract : Reliability test data are presented, which show that non‐oxide all‐lithographic vertical‐cavity surface‐emitting lasers (VCSELs) are more reliable than oxide VCSELs under extreme operating conditions. The test data are compared for lithographic and oxide VCSELs of 3 µm size after operating at a stage temperature of 150°C and an injection current density of 140 kA/cm 2 for various times. The increased reliability under extreme operating conditions can be largely attributed to the lower junction temperature and the internal stress inside lithographic VCSELs.